(untitled) (Sciences & Technology. A, exactes sciences, 2018)
The paper deals with the simulation of dynamical models of constrained multibody systems which can be formulated as a set of Differential Algebraic Equations (DAEs). We consider the general dynamical model resulting from Euler-Lagrange formulation. We investigate the solution with the index reduction method. We illustrate our analysis by the example of the slider-crank mechanism. Among many possible representations, we derive a dynamical model based on two variables offering an easier analysis and implementation. We solve the DAE problem with a Matlab function (ode15s) which is dedicated to solve stiff Ordinary Differential Equations (ODEs). Concordant simulation results have been obtained in comparison to other methods proving an acceptable stability and accuracy of the used method for solving this problem.